Comparative Study of Areca Fiber Reinforced Polyester Composites and Plywood - Islam, Md. Zahidul; Rahman, A.N.M. Masudur; Begum, Hosne Ara (European Scientific Journal, ESJ, 2018)
In this study, the mechanical properties of the composites made of areca fibers as reinforcing agent with polyester matrix were evaluated. Both untreated and treated (mercerized) fibers were used to fabricate composites and the mechanical properties such as tensile strength (TS), tensile modulus (TM), flexural strength (FS), flexural modulus (FM) and impact strength (IS) of the composites were examined. Composites were manufactured by means of hand lay-up technique with varying fiber content (5 and 10%). Mechanical properties of plywood were also tested and compared with the composites. It was found that areca fiber composites showed significant improved mechanical properties than plywood. Among the composite materials 10% fiber loading presented higher mechanical properties than 5% fiber content and the treated fiber composites exhibited enhanced mechanical properties than the untreated fiber composites due to strong interfacial bonding between fiber and matrix. In addition, water uptake test was performed and specifies that areca composites absorbed very much lower amount of water than that of plywood. The morphology was investigated by scanning electron microscopy (SEM).